Perceived Uniqueness and Perceived Value in Shaping Revisit Intention toward Instagrammable Cultural Tourism Destinations - Hamdan Hamdan; M. Rizky Mahaputra; M. Ridho Mahaputra (Greenation Education and Culture Review, 2026)
This study examines the effects of perceived uniqueness and perceived value on revisit intention toward Instagrammable cultural tourism destinations in Jakarta. A quantitative approach with a causal research design was employed using a survey of 237 tourists who had previously visited the destinations through random sampling. The data were analyzed using PLS. The findings indicate that both perceived uniqueness and perceived value positively and significantly influence revisit intention, with perceived value exerting a stronger effect. These findings highlight that destination uniqueness and tourists’ perceived value are critical drivers of repeat visitation. This study contributes to the tourism literature by extending the understanding of tourist behavior in the context of urban Instagrammable tourism and offers practical implications for destination managers in designing authentic, valuable, and sustainable tourism experiences.